LIMBAH PENYULINGAN MINYAK KAYU PUTIH SEBAGAI ENERGI ALTERNATIF: KAJIAN AWAL - Corryanti Triwahyuningsih; Diana Puspitasari; Iwan Gunawan (PROSIDING SNAST, 2018)
Perum Perhutani has an eucalyptus refinery factory, located in several working areas, with a capacity of between 3,000-12,000 tons per year. In the process leaves leaves as waste. This waste is not easily destroyed, so piled mounts around the factory. It is interesting to use it as a renewable alternative energy, in line with the increasing scarcity of fossil fuels. This preliminary study was aimed to know the energy potential of the eucalyptus oil refinery waste. Waste is tested as charcoal briquettes, leaf pellets, and activated charcoal. Charcoal briquettes were tested with three adhesive concentration treatments. The leaf pellet was tested with three temperature treatment forging. Activated charcoal was tested with three activation temperature treatments. Parameters measured were moisture content, ash content, flying substance, density, bound carbon, calorific value. The results show that from charcoal briquettes only the water content that meets the standard. The calorific value of the charcoal briquette from the distillation waste is still below the standard, which is 4,531 cal / g. The results of leaf pellets that meet the standards of charcoal briquettes are moisture content, ash content and density. The calorific value of pellets is 4,851.3 cal / g. The result of the activated charcoal from the distillation waste indicates only the moisture content and the substance of flying meet the standard. The absorption value has not met the standard. This study shows the potential of eucalyptus oil refinery as an alternative energy. Further experiments to obtain quality as required.